"The isolation and estimation of low molecular weight N-nitrosamines in biological materials" - Du Plessis, Leo Stephen (Rhodes University, Faculty of Science, Department of Chemistry, 1973)
Summary: Low molecular weight N-nitrosamines were detected by ultraviolet, infrared, nuclear magnetic resonance, mass spectral, thin-layer chromatographic and gas liquid chromatographic means. A method for the estimation of dimethylnitrosamine, diethylnitrosamine, ethal-n-propylnitrosamine and di-n-propylnitrosamine has been developed. The method involves the isolation of the nitrosamines in an aqueous distillate by freeze-drying. After extraction of the nitrosamines from the aqueous distillate by means of dichloromethane, their separation and quantitative estimation are achieved by gas liquid chromatography of the extract. The procedure can be extended down to the ppb range. Dimethylnitrosamine was isolated from an extract of Solanum incanum and identified by gas liquid chromatography on four different columns, infrared and nuclear magnetic resonance spectroscopy.
Keywords: Uncatalogued